KARAKTERISTIK KIMIA DAN ORGANOLEPTIK MARMALADE KOMBINASI SARI BUAH JERUK MANIS DAN SARI BUAH PALA - Salenussa, Regina; Sipahelut, Sophia Grace; Augustyn, Gelora Helena (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2022)
ABSTRACT Sweet oranges are very popular because of their sweet taste and high nutritional content. One of the citrus products is marmalade. In making marmalade, pectin is needed to get a good gel. One source of natural pectin that can be used is nutmeg juice. The purpose of this study was to study the effect of the ratio of sweet orange juice and nutmeg juice on the chemical and organoleptic characteristics of marmalade. This study was designed using a completely randomized design (CRD) with one factor, namely the ratio of sweet orange juice and nutmeg juice, with four treatment levels: sweet orange juice 20%: nutmeg juice 80%, sweet orange juice 40%: juice nutmeg 60%, sweet orange juice 60%: nutmeg juice 40%, and sweet orange juice 20%: nutmeg juice 80%. Parameters analyzed included vitamin C content, total dissolved solids, water content, ash content, pH and organoleptic tests (color, aroma, taste, and texture). The results showed that marmalade made from the ratio of sweet orange juice and nutmeg juice had vitamin C levels ranging from 33.90-47.75 mg/100 g, total soluble solids 34.35-41.650Brix, water content 20.50-100 g. 25.59%, ash content 0.01-0.37%, pH 3.90-4.25. The ratio of 20% orange juice and 80% nutmeg juice produced the highest levels of vitamin C, with a taste and aroma that the panelists preferred compared to other samples. Keywords: sweet orange juice, nutmeg juice, marmalade ABSTRAKJeruk manis banyak digemari karena rasanya manis dan memiliki kandungan gizi yang tinggi. Salah satu produk dari jeruk adalah marmalade. Dalam pembuatan marmalade, diperlukan pektin untuk mendapatkan gel yang baik. Salah satu sumber pektin alami yang dapat digunakan adalah sari buah pala. Tujuan penelitian ini adalah untuk mempelajari pengaruh ratio sari buah jeruk manis dan sari buah pala terhadap karakteristik kimia dan organoleptik marmalade. Penelitian ini didesain menggunakan Rancangan Acak Lengkap (RAL) satu faktor, yaitu rasio sari buah jeruk manis dan sari buah pala, dengan empat taraf perlakuan: sari buah jeruk manis 20% : sari buah pala 80%, sari buah jeruk manis 40% : sari buah pala 60%, sari buah jeruk manis 60% : sari buah pala 40%, dan sari buah jeruk manis 20% : sari buah pala 80%. Parameter yang dianalisis meliputi kadar vitamin C, total padatan terlarut, kadar air, kadar abu, pH dan uji organoleptik (warna, aroma, rasa,dan tekstur). Hasil penelitian menunjukkan bahwa marmalade yang dibuat dari rasio sari buah jeruk manis dan sari buah pala memiliki kadar vitamin C berkisar 33,90-47,75 mg/100 g, total padatan terlarut 34,35-41,650Brix, kadar air 20,50-25,59%, kadar abu 0,01-0,37%,pH 3,90-4,25. Ratio sari buah jeruk 20% dan sari buah pala 80% menghasilkan kadar vitamin C tertinggi, dengan rasa dan aroma yang lebih disukai panelis dibandingkan sampel lain. Kata Kunci : Sari buah jeruk manis, Sari buah pala, Marmalade